ENVIRONMENTAL QUALITY ON SURROUNDING COMMUNITY OF COAL MINING AREA IN SAMARINDA, EAST KALIMANTAN, INDONESIA - Anggraeni, Ike; Nurrachmawati, Annisa; Ifroh, Riza Hayati; Anwar, Andi; Siswanto, Siswanto (YCAB Publisher & IAKMI SULTRA, 2019)
Background: The massive exploration of coal in Samarinda could lead to various environmental consequences, such as metal contamination of soil, toxic materials and sediments in rivers and air pollution. Scanning and exploring the impact of mining on environmental quality will strategic to develop and carry out rehabilitation on damaged ecosystems and as a preventive and adaptive action of the community in responding the threat of global environmental change.Objective: This paper mainly focused on determining environmental quality based on water and air quality parameters (sulfur dioxide/SO2, Nitrogen dioxide/NO2, Carbon monoxide CO and TSP/dust) also determining community perception about the environment.Methods: Water sample taken from Betapus river (upstream and downstream) and well. Air sample taken around residential in coal mining area. Household survey of 305 respondents conducted in five community neighborhoods in area that affected by mining activities. In general, the air quality parameters such as SO2, NO2, CO and TSP at normal condition.Result: The measurement result of wells water revealed that only the pH (power of hydrogen) at normal condition, while BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), Iron (Fe) exceed the threshold and almost all water sample exceeds the threshold in Manganese (Mn). The results of river quality in pH and COD showed that both in the upstream, midstream and downstream on normal condition, while Fe, COD exceeds the threshold. The BOD in the upper, middle parts of the river exceed the threshold.Conclusion: This study found that there had been anomaly in water environment compounds. These indicate that mining has led to the occurrence of water pollution. Therefore, needs reevaluation analysis of environmental impacts document of the mining companies in Bayur Village. It is also important to treating Mn and Fe of well or river water, especially if the water use for drinking.